The Influence of Brand Credibility towards Words of Mouth of Fashion Brand - Shindy Shindy; Evo Sampetua Hariandja (Universitas Hayam Wuruk Perbanas, 2020)
This research tries to examine the factors influencing the positive word of mouth of Indonesian’s consumer towards fashion brand. The factors studied include brand credibility and brand-self connection as independent variables, brand-self connection and brand-social connection as the mediating variables, and memorial brand experience as the moderating variable. This study is quantitative research with data collection method using the electronic questionnaires of Google forms. This study uses 300 respondents of Prada Italian brand in Indonesia and the data is analyzed using structural equation modelling. The results show that brand credibility, brand self-connection, and brand social connection have a positive effect on word of mouth. Both brand self-connection and brand social connection mediate the influence of brand credibility on word of mouth. This study suggests that by preserving the relationships with consumers as well as consumer relationships with other consumers, managers would be able to produce more positive word of mouth.